Types of Organization Culture that is Important and Relevant for the Success of SME’s Entrepreneur (Case Study in the Creative Economy Entrepreneurs in Jakarta) - Gunawan, Aristo Surya; Cahayani, Ati (Yayasan Sinergi Kawula Muda, 2025)
An organization is a group of people as members that accepts, respects and implements certain same values or norms called organizational culture. MSMEs as business also have organizational culture. Organizational culture is the key to the success because positive organizational culture will form the positive individual character of the organization and vice versa. and the better cultural values in the organization, the better the organization performance. This article will observe the organizational culture that determines business success among creative economy entrepreneurs in Jakarta. This research is descriptive research with quantitative and qualitative data analysis. Quantitative data was obtained through the distribution of questionnaires to 150 respondents of creative economy entrepreneurs in Jakarta. Qualitative data was obtained through interviews to 15 selected informants. The results of the quantitative analysis showed that the dimension of attention to detail and team orientation have the highest scores, besides that, respondents also considered stability as an important aspect to achieve success. In line with the quantitative analysis, qualitative analysis also shows that teamwork is important because businesses cannot be successful if they rely on individual performance or achievements.